EFEKTIVITAS TADOKU TERHADAP KEMAMPUAN HIRAGANA PADA SISWA KELAS XI SMAN 4 PEKANBARU - Indria Apriza (Vocational College of Diponegoro University, 2022)
This study aims to determine the effectiveness of using Tadoku in improving Hiragana skills in class XI students of SMAN 4 Pekanbaru. The population in this study were students of class XI IPA 3 with a total of 36 students and XI IPA 5 with a total of 36 students at SMAN 4 Pekanbaru, totaling 72 students. The samples taken by the researchers in this study were 18 students in class XI IPA 5 as the experimental class and 18 students in class XI IPA 3 as the control class with a total of 36 people. The results showed that Tadoku has effective in improving hiragana skills in class XI students of SMAN 4 Pekanbaru